Oncolytic NDV-AMHA1 Strain Effective Against Glioblastoma Cancer Cells - Zahraa Kadhim; Ghassan Sulaiman; Ahmed Al-Shammari; Hamdoon Mohammed; Salman Mohammed (Journal of Applied Sciences and Nanotechnology, 2023)
Glioblastoma multiforme (GBM) is one of the most life-threatening types of cancer that is difficult to treat. The search for effective yet safe therapy is progressing and non-conventional therapies such as using viruses as a smart and selective agent against cancer are promising. The aim of the study was the presence of a reliable method to use Newcastle disease virus (NDV) as an oncolytic agent against GBM, which attempted to propagate the NDV in laboratory experiments. Ahmed Majeed Hamza Al-Shammari-1 (AMHA1) attenuated strain of NDV was propagated in chicken embryos. The virus's tittered in Vero-slamed cells to determine the infective dose. MTT cell viability assay was used to investigate the killing effects of NDV on Ahmed-Majeed-Glioblastoma-Multiforme-2005 (AMGM5) human glioblastoma cancer cells derived from Iraqi patients. The infected cells' morphology was studied to measure the cytolytic effect of the NDV in cancer cells. Results showed that After 24 to 72 hours of inoculation, all of the chicken embryos died when the AMHA1 Iraqi NDV strain was injected. Cell viability assay showed that the NDV-AMHA1 strain has cytotoxicity at MOI of 0.1, 0.5, and 1 for 72 hours of exposure to cancer cells. The morphological analysis showed that NDV induces cell death in the infected cells with both necrotic and apoptotic features. In conclusion, the study focuses on the propagation of the oncolytic NDV as a biological agent capable of overcoming treatment resistance through infecting and replicating inside cancer.